The Effect of Ability, Motivation and Commitment on Employee Performance at KPP Pratama Jember - Alfien Prasetya Eryngga (Dinasti International Journal of Education Management And Social Science, 2023)
This literature review article entitled The Effect of Ability, Motivation and Commitment on Employee Performance is a scientific article that aims to build a hypothesis regarding research on the influence between variables that will used in further research , within the scope of Human Resource Management science. The method of writing this Literature Review article is the library research method , which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this literature review are: 1) ability to influence employee performance; 2) motivation influences employee performance; and 3) commitment affects employee performance.